2021
DOI: 10.1136/ijgc-2021-002622
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy in elderly women with epithelial ovarian cancer: analysis of a prospective registry

Abstract: ObjectiveTo evaluate perioperative outcomes in elderly versus non-elderly women with advanced or recurrent epithelial ovarian cancer undergoing surgery with hyperthermic intraperitoneal chemotherapy (HIPEC).MethodsA single-institution prospective registry was analyzed for women with ovarian cancer who underwent surgery with HIPEC from January 2014 to December 2020. Elderly age was defined as ≥65 years at surgery. Complications were defined according to the Accordion scale. Univariate and multivariable analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Enhanced recovery after surgery is used postoperatively, and patients are cared for on the routine surgical floor. Other institutions have published guides to starting HIPEC protocols, most of which focus on perioperative care and considerations, as well as the multidisciplinary work needed to achieve a safe and efficacious HIPEC case [33–35,36 ▪ ,37–41].…”
Section: Perioperative Considerations When Administering Hyperthermic...mentioning
confidence: 99%
“…Enhanced recovery after surgery is used postoperatively, and patients are cared for on the routine surgical floor. Other institutions have published guides to starting HIPEC protocols, most of which focus on perioperative care and considerations, as well as the multidisciplinary work needed to achieve a safe and efficacious HIPEC case [33–35,36 ▪ ,37–41].…”
Section: Perioperative Considerations When Administering Hyperthermic...mentioning
confidence: 99%
“…In a meta-analysis on cytoreductive surgery and HIPEC regardless of the indication which considered different cut-offs (65, 70, 75 years) to analyze the effect of age on patients’ outcomes and toxicities, the 70 year threshold appeared to be clinically relevant; the 30-day postoperative grade 3 morbidity and the 90-day postoperative mortality were significantly higher in patients ≥70 years, although this was not associated with a longer hospital stay [ 58 ]. In a recent single-institution prospective analysis of HIPEC in patients with gynecologic cancers, Chambers et al found that chronological age (<65 vs. ≥65 years) did not predict post-operative complications, progression-free survival or overall survival but that patients aged ≥70 years had a reduced progression-free survival following HIPEC compared to patients 65–69 years without any impact on overall survival [ 59 ]. However, the same group later reported that a composite index of 11 medical comorbidities (the modified frailty index, mFI) significantly predicted post-operative complications in multivariate analysis, with a more than 9-fold risk of grade ≥2 complications in those with mFI ≥ 2 vs. 0–1 (OR 9.4, 95% CI [3.3; 26.4], p < 0.001), whereas age did not [ 60 ].…”
Section: Surgerymentioning
confidence: 99%